Stress adaptation in Talaromyces marneffei - Pongpom, Monsicha; Vanittanakom, Nongnuch (Biomedical Sciences and Clinical Medicine, 2024)
Talaromyces marneffei (T. marneffei) (previously named Penicillium marneffei) is a thermal dimorphic fungus that causes disseminated infection, which is common in AIDS patients, especially in northern Thailand. This fungus has the ability to survive in a host macrophage, which is the virulence factor attributed to promoting pathogenicity. At present, understanding of T. marneffei stress response in vivo is limited. Therefore, this study analyzed genes that are responsible for stress. They are highly expressed during the pathogenic yeast phase and encoded antigenic proteins of T. marneffei. Expression patterns of genes encoded for heat shock protein 30, glutathione peroxidase, cytochrome c oxidase and NADH-ubiquinone oxidoreductase were different in the mold, conidial and yeast phase. Interestingly, genes responsible for heat shock and nutrient starvation had lowest activity in the mold phase instead of the conidial phase. This result suggested that, even in the dormant stage, the conidia of this fungus prepared the genes responsible for several stresses, and they may play a role in the germination and survival process during infection. This study hypothesized that this pathogen has the ability to resist complex and dynamic host niches by occupying alternative carbon sources and having simultaneous response to heat and oxidative stresses inside the host.